FIRST CASE OF HUMAN INFECTION BY Bertiella studeri (Blanchard, 1891) Stunkard,1940 (Cestoda; Anoplocephalidae) IN BRAZIL - LOPES, Valeriana Valadares; SANTOS, Hudson Andrade dos; SILVA, Amália Verônica Mendes da; FONTES, Gilberto; VIEIRA, Gabriela Lisboa; FERREIRA, Arilton Carlos; SILVA, Eduardo Sergio da (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
Cestodes of the Bertiella genus are parasites of non-human primates found in Africa, Asia, Oceania and the Americas. Species Bertiella studeri and Bertiella mucronatacould, accidentally, infect human beings. The infection occurs from ingestion of mites from the Oribatida order containing cysticercoid larvae of the parasite. The objective of this report is to register the first case of human infection by Bertiella studeri in Brazil. Proglottids of the parasite, found in the stool sample of a two-and-a-half-year-old child, were fixed, stained and microscopically observed to evaluate its morphological characteristics. Eggs obtained from the proglottids were also studied. The gravid proglottids examined matched the description of the genus Bertiella. The eggs presented a round shape, with the average diameter of 43.7 µm, clearly showing the typical pyriform apparatus of B. studeri. The authors concluded that the child was infected with Bertiella studeri,based on Stunkard's (1940) description of the species. This is the fifth case of human Bertiellosis described in Brazil through morphometric analysis of the parasite, the third in Minas Gerais State and the first diagnosed case of Bertiella studeriin Brazil.